SharePoint 2003 User’s Guide - Bates, Seth (Apress, 2013)
SharePoint 2003 is quickly becoming more prevalent in the workplace, and all types of business professionals are becoming involved in using and managing SharePoint-based resources. We have seen many situations where, after SharePoint is introduced, individuals struggle to leverage these resources without a good enough understanding of the capabilities to gain the most value possible. SharePoint 2003 User’s Guide was an outcome of this need, and our book can serve as a reference for people working within a SharePoint environment. The goal of this book is to deliver a tool to all levels of SharePoint users. Beginners will be supplied with the information they need to most effectively use SharePoint’s capabilities. Intermediate users will be given the information they need to manage their SharePoint resources. Advanced users will be provided the foundation needed for building business solutions using SharePoint’s capabilities. We have spent a great deal of effort putting our experiences working with a variety of organizations and knowledge of the product into an easily understood format for learning about SharePoint 2003, which we hope will enable you to gain the in-depth knowledge you need to effectively use and manage these tools. Further reading about the topics provided in this book can be found at http:// www.sharepointextras.com where we provide additional information about SharePoint including references to other resources.